2017
DOI: 10.1186/s40360-017-0137-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of diacetyl-liensinine on electrophysiology in rabbit ventricular myocytes

Abstract: BackgroundDiacetyl-liensinine is a chemosynthetic derivative of liensinine, extracted from the seed embryo of Nelumbo nucifera Gaertn, in China. It has been found to have extensive anti- arrhythmic actions. The present study was designed to investigate the effects of diacetyl-liensinine on electro- physiology of myocytes.MethodsWe exposed rabbit ventricular myocytes to diacetyl-liensinine using standard whole-cell patch-clamp technique and measured the action potential, L-type calcium current (I Ca-L), delayed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…4, IL did not affect these currents, avoiding the risks of lead to arrhythmia. It has been reported that liensinine, the isomer of IL, can inhibit I K1 and I K [35][36][37]. This difference may be caused by the otherness between isomers.…”
Section: Discussionmentioning
confidence: 98%
“…4, IL did not affect these currents, avoiding the risks of lead to arrhythmia. It has been reported that liensinine, the isomer of IL, can inhibit I K1 and I K [35][36][37]. This difference may be caused by the otherness between isomers.…”
Section: Discussionmentioning
confidence: 98%
“…Traditional Chinese medicine (TCM) has been widely used to treat various diseases for thousands of years. Among them, liensinine, a natural isoquinoline alkaloid, can be isolated from a Chinese medicinal herb (Nelumbo nucifera Gaertn) and possesses several medicinal benefits [ 6 8 ]. Increasing evidence shows that liensinine may be a potential antitumor agent, and its efficacy against human colorectal, gallbladder, and breast cancers has been validated by previous studies [ 6 , 9 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Liensinine, a natural isoquinoline alkaloid, is isolated from the seed embryo of Nelumbo nucifera Gaertn [ 6 ]. Multiple biological effects of liensinine are reported in recent pharmacological studies, including antihypertension and antiarrhythmias, as well as anticancer properties [ 6 8 ]. For example, liensinine can induce apoptosis and growth cessation of gallbladder cancer [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Alkaloids are the major constituents of lotus [ 7 ]. Similar to other bisbenzylisoquinoline alkaloids such as isoliensinine and neferine, liensinine also exhibits anti-HIV [ 8 ], antiarrhythmic [ 9 , 10 ], anti-inflammatory [ 11 , 12 ], antipyretic [ 13 ], anticancer [ 14 ], antidepressant [ 15 , 16 ], and antihypertensive [ 17 ] properties.…”
Section: Introductionmentioning
confidence: 99%